ASSESSMENT OF HEAVY METAL LOAD IN FRUITS AND VEGETABLES CONSUMED IN AND AROUND ANAMBRA STATE POLYTECHNIC, MGBAKWU - R.O., Ezebo; C.F., Ifeanyi; O.U., Obieze, (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Fruits and vegetables are of plant source and are consumed a lot by human and animals. Fruits and vegetables could be contaminated with heavy or toxic metals through contaminated soil and water with these heavy metals. Contaminated fruits and vegetables consumed by man and animals will gradually build up of this toxins and if not detoxified faster in the body will build up to a concentration higher than the permissible level (Zurbrugg et al., 2003). Human activities such as industrial production, mining, agriculture and transportation release a high amount of heavy metals to the biosphere. The primary sources of metal pollution are the burning of fossil fuels, smelting of metal like ores, municipal wastes, fertilizers, pesticides and sewage (Xiaoli, 2007; Radwan and Salama, 2006; Wilson and Pyatt, 2007). The purpose of this quantitative study was to examine the level of heavy metal load of fruits and vegetables consumed in and around Anambra State Polytechnic, Mgbakwu, Southeast Nigeria. Local officials may utilize this study's results to develop a standard that can improve the quality of commercially sold fruits and vegetables in and around the locality.